The Role of the Instagram Application in Increasing Brand Awareness in Companies - Dewi Indriani Jusuf (SEAN Institute, 2022)
This research aims to explore the role played by the social media platform Instagram in increasing brand awareness for companies. With the increasing use of social media as a marketing and communication tool, Instagram has become one of the main platforms used by companies to expand their audience reach and increase their brand awareness. This research uses a qualitative approach with descriptive methods. The research results show that using Instagram effectively can increase brand awareness and expand marketing reach for companies. By leveraging features such as engaging visual content, use of relevant hashtags, paid advertising options, and collaboration with influencers, companies can strengthen their brand identity, increase user engagement, and expand brand influence among a wider audience. Thus, Instagram has proven to be an effective and important tool for companies in expanding their marketing reach, building closer relationships with consumers, and increasing brand awareness in the ever-evolving digital era.